2021
DOI: 10.1002/adma.202102822
|View full text |Cite
|
Sign up to set email alerts
|

Response to Comment on “Eppur si Muove: Proton Diffusion in Halide Perovskite Single Crystals”: Measure What is Measurable, and Make Measurable What is Not So: Discrepancies between Proton Diffusion in Halide Perovskite Single Crystals and Thin Films

Abstract: Buffeteau et al. note that the proton diffusion coefficient in MAPbI3 that is deduced (by the authors) from results, obtained by a suite of complementary techniques, on a large number of single crystals (Adv. Mater. 2020, 32, 2002467) is 5 orders of magnitude higher than what is estimated (by them) in J. Am. Chem. Soc. 2020, 142, 10431, from infrared spectroscopy on ultrathin MAPbI3 films; use of (deuterium/hydrogen) D/H isotope substitution is common to both studies. Buffeteau et al. speculated that proton di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Consistent with our earlier work, [39,45] where we found that H + migration in the bulk is enhanced in the presence of H 2 O, we find that the self-healing reaction is more rapid in more humid than in drier ambient (cf. Figure 1b with Figure 1a).…”
Section: Ch Nh Pbsupporting
confidence: 92%
“…Consistent with our earlier work, [39,45] where we found that H + migration in the bulk is enhanced in the presence of H 2 O, we find that the self-healing reaction is more rapid in more humid than in drier ambient (cf. Figure 1b with Figure 1a).…”
Section: Ch Nh Pbsupporting
confidence: 92%
“…We now compare the rate of atomic-scale exchange of 2 H + ions between MA + cations, as measured here, and the previously measured diffusion rates for bulk exchange of 1 H/ 2 H in MAPbI 3 single crystals and thin films (Table ). , The range of reported values covers several orders of magnitude, as has been discussed previously, , which could reflect differences between the H + diffusivity in thin films and large single crystals, as well as differences in hydration, solvation, and surface passivation. These factors are also likely to be different for the microcrystalline powders studied here; nevertheless, significant insight can be gained from a semiquantitative comparison.…”
Section: Resultsmentioning
confidence: 57%
“…where each HC(NH 2 )NH-Pb 2+ can be seen as a vacancy of H + inside FAPbBr 3 . [21,22] As the addition of methylamine to methylammonium-based perovskites has been shown to improve their quality, [56] an equivalent improvement in degraded FAPbBr 3 is expected once formamidine is formed through reaction (5). Of course, complete self-healing of FAPbBr 3 is disfavored at the surface due to the loss of gaseous Br 2 but can occur in the bulk, as the following PL data demonstrate.…”
Section: Irradiation Of Pristine Fapbbr 3 Filmsmentioning
confidence: 88%
“…[14][15][16][17][18] These processes originate from the low activation energies of chemical reactions and migration of ionic species in APbX 3 perovskites. [19][20][21][22][23][24][25][26][27] Anions are the most mobile species, while Pb 2+ is found to be the slowest moving species. [28,29] APbX 3 perovskites incorporating FA + and Br − ions display higher stability than other compositions under external stresses.…”
Section: Introductionmentioning
confidence: 92%